If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + 41 = 29x + -3 Reorder the terms: 41 + 18x = 29x + -3 Reorder the terms: 41 + 18x = -3 + 29x Solving 41 + 18x = -3 + 29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29x' to each side of the equation. 41 + 18x + -29x = -3 + 29x + -29x Combine like terms: 18x + -29x = -11x 41 + -11x = -3 + 29x + -29x Combine like terms: 29x + -29x = 0 41 + -11x = -3 + 0 41 + -11x = -3 Add '-41' to each side of the equation. 41 + -41 + -11x = -3 + -41 Combine like terms: 41 + -41 = 0 0 + -11x = -3 + -41 -11x = -3 + -41 Combine like terms: -3 + -41 = -44 -11x = -44 Divide each side by '-11'. x = 4 Simplifying x = 4
| 40x+4y=-8 | | 6x+66=2x+30 | | -144+14x+y=-168+17x+y | | -x-3=4x+2 | | -2x+41=2x+17 | | 3u+2=-19 | | 1/4-5/3 | | 9-6:-1/3-3 | | 3x^2-6x+5=2x(4-x) | | 3X+2x=4a | | -396/x-10=-22 | | graphy=90-x | | 9x-2(4-2x)=7x+16 | | y=90-x | | 4/7(56) | | 9x^3+35x^2+51x+36=0 | | 16x-21=12x-15 | | Y=12-2(5) | | 5/9/4/5 | | (5-3x)-(-4x+6)=(8x+11)-(-3x-6) | | 1000=0.1x+x | | 15(m-3)=90 | | Y=12-2(4) | | k+90=105 | | 6/7d-5=3/7d-2 | | 17+k=29 | | 1.6-4.8=-1.6 | | 2x+(2x+1)=8+(3x+3) | | 73/24=45/x | | 73/24=125/x | | 73/24=41/x | | 73/24=100/x |